2016
DOI: 10.1097/j.pain.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Trends and predictors of opioid use after total knee and total hip arthroplasty

Abstract: Few studies have assessed postoperative trends in opioid cessation and predictors of persistent opioid use after total knee arthroplasty (TKA) and total hip arthroplasty (THA). Preoperatively 574 TKA and THA patients completed validated, self-report measures of pain, functioning and mood and were longitudinally assessed for 6-months post-surgery. Among patients who were opioid naïve the day of surgery, 8.2% of TKA and 4.3% of THA patients were using opioids at 6 months. In comparison, 53.3% of TKA and 34.7% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
367
1
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 418 publications
(415 citation statements)
references
References 22 publications
(33 reference statements)
28
367
1
7
Order By: Relevance
“…Patients taking greater than 60mg oral morphine equivalents preoperatively have an 80% likelihood of chronic use 6 months after total knee or hip arthroplasty. 67 …”
Section: Predictors Of Chronic Opioid Use After Surgerymentioning
confidence: 99%
“…Patients taking greater than 60mg oral morphine equivalents preoperatively have an 80% likelihood of chronic use 6 months after total knee or hip arthroplasty. 67 …”
Section: Predictors Of Chronic Opioid Use After Surgerymentioning
confidence: 99%
“…acute tolerance) [6,7]. In a recently published study [8], investigators reported that for many patients taking opioids before joint replacement surgery, as well as some opioid-naïve patients undergoing arthroplasty procedures, opioid use persisted after surgery despite the absence of joint pain. Retrospective studies have also found an association between the use of large doses of opioid analgesic medication during the perioperative period in patients undergoing primary tumor resections and the recurrence of cancer within 5 years [9].…”
Section: Introductionmentioning
confidence: 99%
“…2,4446 Indeed, work by Goesling and others has demonstrated a much longer duration and consistency of use of opioids following common orthopaedic surgeries than commonly anticipated, often associated with transformation of use patterns from treatment of postoperative pain to treatment of extra-surgical maladies; other related work has demonstrated substantial negative impact of preoperative opioids on postoperative recovery across a range of surgical models. 2,4750 Economically, this phenomenon further highlights how seemingly cost-effective short-term solutions can lead to drastically increased long-term costs. These costs are often transferred to others within the community and extend beyond healthcare costs to other societal concerns such as law enforcement, employment, and even defense; the cost-effectiveness discussion is thus not constrained to the individual patient, but bridges the conceptual boundaries between personal and population health.…”
Section: Payer Modelsmentioning
confidence: 99%